Exploration of microbiome diversity of stacked fermented grains by flow cytometry and cell sorting - Zhang, Ziyang; Wei, Yanwei; Peng, Zehao; Du, Peng; Du, Xinyong; Zuo, Guoying; Wang, Chaoqing; Li, Piwu; Wang, Junqing; Wang, Ruiming (Frontiers in Microbiology, 2023)
Sauce-flavor baijiu is one of the twelve flavor types of Chinese baijiu. Microbial composition plays a key role in the stacked fermented baijiu using grains as the raw materials and the formation of flavor substances, however, the active microbial community and its relationship remain unclear. Here, we investigated the total and active microbial community of stacked fermented grains of sauce-flavored Baijiu using flow cytometry and high-throughput sequencing technology, respectively. By using traditional high-throughput sequencing technology, a total of 24 bacterial and 14 fungal genera were identified as the core microbiota, the core bacteria were Lactobacillus (0.08%-39.05%), Acetobacter (0.25%-81.92%), Weissella (0.03%-29.61%), etc. The core fungi were Issatchenkia (23.11%-98.21%), Monascus (0.02%-26.36%), Pichia (0.33%-37.56%), etc. In contrast, by using flow cytometry combined with high-throughput sequencing, the active dominant bacterial genera after cell sorting were Herbaspirillu, Chitinophaga, Ralstonia, Phenylobacterium, Mucilaginibacter, and Bradyrhizobium, etc, the active dominant fungal genera detected were Aspergillus, Pichia, Exophiala, Candelabrochaete, Italiomyces, and Papiliotrema, etc, These results indicate that although the abundance of Acetobacter, Monascus and Issatchenkia were high after stacked fermentation, they may have little biologically active. The results also showed that the flow cytometry and cell sorting method is convenient for rapid monitoring of complex microbial flora and can assist in exploring more complex environmental samples.